Upaya Meningkatkan Kompetensi Guru Madrasah Ibtidaiyah Di Kecamatan Pucakwangi Dalam Merancang Model Pembelajaran Make A Match Melalui Workshop - maryati maryati (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2023)
Efforts to Improve the Competence of Madrasah Ibtidaiyah Teachers in Pucakwangi District in Designing Make a Match Learning Models Through Workshops. The purpose of this study was to describe the response of Madrasah Ibtidaiyah teachers in the Pucakwangi District in designing the Make a Match learning model through a workshop. From the results of the analysis, information was obtained that there was an increase in the ability of Islamic elementary school teachers in the Pucakwangi sub-district, Pati district in designing the Make a Match (MM) Learning Model. This increase was shown by (1) the competence of primary school teachers in Pucakwangi sub-district, Pati district in compiling the characteristics of the Make a Match (MM) Learning Model, from 13% in cycle I to 100% in cycle II; (2) the competence of primary school teachers in the Pucakwangi sub-district, Pati district in formulating the elements of the Make a Match (MM) Learning Model, from 13% in cycle I to 100% in cycle II; (3) the competency of primary school teachers in Pucakwangi sub-district, Pati district in compiling characteristics in the Make a Match (MM) Learning Model, from 20% in cycle I to 100% in cycle II; (4) the competence of primary school teachers in the Pucakwangi sub-district, Pati district in developing the principles of the Make A Match (MM) Learning Model, from 13% in cycle I to 100% in cycle II; (5) the competency of primary school teachers in Pucakwangi sub-district, Pati district in compiling steps in the Make A Match (MM) Learning Model, from 13% in cycle I to 100% in cycle II.